The Behaviour of Mistuned Piezoelectric Shunt Systems and Its Estimation - M. Berardengo; S. Manzoni; M. Vanali (Shock and Vibration)
This paper addresses monoharmonic vibration attenuation using piezoelectric transducers shunted with electric impedances consisting of a resistance and an inductance in series. This type of vibration attenuation has several advantages but suffers from problems related to possible mistuning. In fact, when either the mechanical system to be controlled or the shunt electric impedance undergoes a change in their dynamical features, the attenuation performance decreases significantly. This paper describes the influence of biases in the electric impedance parameters on the attenuation provided by the shunt and proposes an approximated model for a rapid prediction of the vibration damping performance in mistuned situations. The analytical and numerical results achieved within the paper are validated using experimental tests on two different test structures.